Pelatihan Kewirausahaan Kreatif bagi Ibu Rumah Tangga melalui Produksi Batik Eco Print di Desa Ngeper Padangan - Mujiarto; Luluk Atul Azizah (CV. Agrapana Media, 2025)
The Creative Entrepreneurship Training for Housewives through Eco Print Batik Production in Ngeper Village, Padangan is a community empowerment initiative aimed at enhancing the skills, creativity, and economic independence of rural women by utilizing the potential of local natural resources. This activity was motivated by the low economic participation of housewives and the abundance of natural resources that have not been optimally utilized. The implementation method consisted of four main stages: socialization, training, evaluation, and program sustainability. The socialization phase was carried out to build participants’ understanding and motivation, while the training focused on hands-on practice in making eco print batik — from selecting natural materials and applying printing techniques to packaging products with market value. Evaluation was conducted through pre-tests and post-tests to measure participants’ skill improvement. The results showed a significant increase in knowledge, technical skills, and entrepreneurial motivation, with an average score improvement of 34.85%. Participants also demonstrated high creativity in designing local motifs and a growing awareness of environmental preservation. The follow-up plan focuses on establishing a joint business group, providing continuous mentoring, and building strategic partnerships with government and private institutions. Thus, this training program not only succeeded in fostering skills and entrepreneurial spirit but also created new economic opportunities based on local potential and environmental sustainability principles.